Uji Aktivitas Antibakteri Ekstrak Etanol Bunga Gemitir (Tagetes erecta Linn.) terhadap Bakteri Staphylococcus aureus dan Escherichia coli - Marsah, Unggu Putri Six; Ramandha, Muhammad Eka Putra; Pratiwi, Baiq Yulia Hasni (Biocity Journal of Pharmacy Bioscience and Clinical Community, 2024)
Gemitir flowers (Tagetes erecta Linn.) contain secondary metabolite compounds such as flavonoids, phenolics, saponins and carotenoids which have the potential as antibacterials that can be used in treating infections caused by pathogenic bacteria Staphylococcus aureus and Escherichia coli. The purpose of this study was to determine the effective concentration of etanol extract of gemitir flowers and the comparison of antibiotic inhibition with etanol extract of gemitir flowers in inhibiting the growth of S. aureus and E. coli bacteria. This study is an experimental study and was analyzed using the One Way ANOVA statistical test. The results showed that gemitir flower extract positively contained secondary metabolites in the form of flavonoids, phenolics and saponins. The antibacterial activity test of etanol extract of gemitir flowers can inhibit S. aureus and E. coli at concentrations of 85%, 90%, 95% and 100% with the diameter of the inhibition zone obtained of 17-31.6 mm which is included in the strong-very strong category. Based on the description above, it can be concluded that the etanol extract of gemitir flowers has the potential to inhibit the growth of S. aureus and E. coli bacteria.